การปฏิบัติธรรมของนักศึกษา ระดับบัณฑิตศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน - พรมศรี, ดร.ประสงค์ (วารสารมนุษยศาสตร์และสังคมศาสตร์ มมร.วิทยาเขตอีสาน; Vol 1 No 2 (2563): ปีที่ 1 ฉบับที่ 2 พฤษภาคม-สิงหาคม 2563, 2020)
บทคัดย่อ การวิจัยเรื่องนี้ มีวัตถุประสงค์ 3 ประการ คือ 1. เพื่อศึกษาการปฏิบัติธรรมตามหลักพระพุทธศาสนา 2. เพื่อศึกษาการปฏิบัติธรรมของนักศึกษาระดับบัณฑิตศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน และ 3. เพื่อสังเคราะห์แนวทางส่งเสริมการปฏิบัติธรรมเพื่อพัฒนาอารมณ์ของนักศึกษาระดับบัณฑิตศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย  วิทยาเขตอีสาน ผลการวิจัยพบว่า : การปฏิบัติธรรมตามหลักพระพุทธศาสนา ได้แก่ 1. การละเว้นความชั่ว การทำความดี และการทำจิตให้บริสุทธิ์ 2. การให้ทาน รักษาศีล และการภาวนา 3. การปฏิบัติสมถและวิปัสสนาภาวนา ส่วนการปฏิบัติธรรมของนักศึกษาระดับบัณฑิตศึกษา มหาวิทยาลัยมหามกุฏราชวิทยาลัย วิทยาเขตอีสาน ได้แก่ การให้ทาน คือ การถวายน้ำปานะ การถวายภัตตาหาร การรักษาศีล คือ รู้จักการสำรวมกาย วาจา ทำความสะอาดที่พักอาศัย  การภาวนา คือ รู้จักคิดพิจารณาหาเหตุผล อ่านหนังสือธรรมะ ฟังธรรม และมีความอดทน แนวทางส่งเสริมการปฏิบัติธรรมเพื่อแก้ไขอารมณ์ คือ 1) ด้านความคิด คือ คิดบวกและศึกษาธรรมะให้มาก 2) กัลยาณมิตร คือ พูดคุยให้เพื่อนสนิทฟังในเรื่องที่อารมณ์ไม่ดีมีมนุษยสัมพันธ์  3) สร้างอารมณ์ดีให้เกิดขึ้น เช่น ฟังดนตรีธรรมชาติบำบัดอยู่คนเดียว เดินเล่นไปตามป่าไม้คนเดียว 4) ยึดธรรมะในการดำเนินชีวิต คือ รู้จักให้อภัย หางานที่ชอบ ปล่อยวาง และปฏิบัติสมถะและวิปัสสนากรรมฐาน แนวทางส่งเสริมการปฏิบัติธรรมเพื่อการพัฒนาอารมณ์ คือ มีระเบียบวินัย ปรับทัศนคติไปในแง่บวก ฝึกสติ สมาธิ เป็นประจำ และ บำเพ็ญประโยชน์เพื่อผู้อื่น การสังเคราะห์แนวทางส่งเสริมการปฏิบัติธรรม จำนวน 4 แนวทาง ได้แก่ 1. การมีสติอยู่ในชีวิตประจำวัน คือ การหลบเลี่ยงอารมณ์ การข่มใจจากอารมณ์ การชนะใจตนเอง การรู้จักคิด 2. การปฏิบัติกรรมฐาน คือการปฏิบัติสมถและกัมมัฏฐาน 3. การมีกัลยาณมิตร คือ การสนทนาธรรม การศึกษาธรรมะ 4. การทำกิจกรรม คือ การบริจาคทาน การออกค่ายปฏิบัติธรรมและการทัศนศึกษาวัด คำสำคัญ :  ปฏิบัติธรรม, อารมณ์ Abstract The objectives of this research were as follows: 1. to study Dhamma according to Buddhist Principle, 2. to study Dhamma practice of graduate students in Mahamakut Buddhist University Isan Campus, and 3. to integrate ways in promoting Dhamma practice to develop moods of graduate students in Mahamakut Buddhist University Isan Campus. The results were as follows : Dhamma practice according to Buddhist principles were: 1. Abstain from doing bad, and purify the mind, 2. Making merit by observing precepts (Sila) and meditation, 3. Practicing Samata (Concentration Development), and 4. Practicing Vipasana. As for the Dhamma practice of graduate students of Mahamakut Buddhist University Isan Campus, they practice: merit making by offering drinks, and giving alms; observing 5 precepts (Sila), pacifying body, speech, and mind while walking, cleaning, temple area, sala, chanting hall, Chedi. Praying means dedication of merits to the relatives; practice endeavors, being reasonable, remembering Buddha, Dhamma, and Sangha, reading Dhamma books, meditation, praying, listening to Dhamma, helping others, and being patience. 1. Ways to develop Dhamma practice were: 1) in the aspect of thinking; be positive and study dhamma, 2) be friendly; talking with your friends about bad moods, 3) create good moods; sleeping, listening to music, strolling around, being with nature and take a rest, 4) stick to Dhamma in living a life; live a life using Dhamma of Buddha, detached and practice Samatha and Vipasana meditation; 2. Ways to develop the moods of graduate students of Mahamakut Buddhist University Isan Campus: 1) be systematic i.e., to observe Sila, meditation regularly; 2) have positive attitude i.e., listen to Dhamma, be conscious, pray, read Dhamma books; 3) practice meditation regularly i.e., be calm, restrain the things which creates bad moods and study Samatha and Vipasana meditation; and 4) do beneficial deeds.    Integrating ways in developing the Dhamma practice in developing moods in 4 ways are as follows: 1. Being conscious in daily life i.e., avoid moods, restraint moods, soothing wisdom, be self-controlled; 2. Meditation i.e., Samatha Meditation, Vipasana Meditation; 3. having good friends i.e., discuss Dhamma, study Dhamma; and 4. Doing activities i.e., making merits, practicing meditation. Key words : Practice Dhamma, Moods